Analisis Komparatif Kesalahan Kognitif dan Penalaran Matematis Siswa pada Soal PISA Level 6 - Chusnul Chatimah Azis; Andi Asrafiani Arafah; Abdul Rahman; Bernard Bernard (FKIP Universitas Mataram, 2026)
This research is motivated by the crucial issue of declining Indonesian PISA scores in 2022, whichraises the urgency to evaluate and understand the disparity in mathematical literacy skills acrosseducational levels. The purpose of this study is to comparatively analyze the cognitive error profilesand mathematical reasoning of junior high and senior high school students in Makassar in solvingmathematical literacy problems equivalent to PISA Level 6. This study uses a qualitativedescriptive method through a comparative case study design. The research subjects consisted ofninth-grade students from two public junior high schools and tenth-grade students from one publicsenior high school in Makassar City. Data were collected using a written essay test instrumentthat adapted the PISA 2022 framework for the content of Quantity, Uncertainty and Data, andChange and Relationships. The written data were then analyzed using a modified Newman ErrorAnalysis procedure. The results highlight significant ability disparities and several cognitiveproblems: (1) at the junior high school level, students tend to stall and make literal errors at thecomprehension and transformation stages; (2) At the high school level, although there is progressin average conceptual understanding, students experience stagnation in critical data literacyevaluation competencies. This finding leads to the conclusion that the pattern of students' writtenerrors indicates the fossilization of misconceptions, where errors in mathematical understandingare not corrected and continue to be carried over from elementary to secondary education.